Modeling SARS‐CoV‐2 proteins in the CASP‐commons experiment. Issue 12 (5th October 2021) - Kryshtafovych, Andriy; Moult, John; Billings, Wendy M.; Della Corte, Dennis; Fidelis, Krzysztof; Kwon, Sohee; Olechnovič, Kliment; Seok, Chaok; Venclovas, Česlovas; Won, Jonghun; ,
Abstract: Critical Assessment of Structure Prediction (CASP) is an organization aimed at advancing the state of the art in computing protein structure from sequence. In the spring of 2020, CASP launched a community project to compute the structures of the most structurally challenging proteins coded for in the SARS‐CoV‐2 genome. Forty‐seven research groups submitted over 3000 three‐dimensional models and 700 sets of accuracy estimates on 10 proteins. The resulting models were released to the public. CASP community members also worked together to provide estimates of local and global accuracy and identify structure‐based domain boundaries for some proteins. Subsequently, two of these structures (ORF3a and ORF8) have been solved experimentally, allowing assessment of both model quality and the accuracy estimates. Models from the AlphaFold2 group were found to have good agreement with the experimental structures, with main chain GDT_TS accuracy scores ranging from 63 (a correct topology) to 87 (competitive with experiment).